Juridical Analysis of Unlawful Acts in a Land Grabbing Case Without Ownership Rights - Rohman Hakim; Bagus Reko Prasetyo; Muhammad Habibur Rochman; Vanda Indarsita (JURNAL HUKUM SEHASEN, 2023)
When carrying out a legal action, of course there must also be legal responsibility. Legal liability is usually always associated with criminal law which is known as the principle (Geen straf zonder schuld; actus non facit reum nisi mens sit rea) of not being punished if there is no mistake. In criminal law, the presence of an error is an absolute element that can result in criminal liability being sought from the perpetrator of the crime. Responsibility for a criminal act committed by a person is to determine the guilt of the criminal act he committed. Criminal responsibility means that a person who has committed a criminal act does not necessarily have to be punished. He must be responsible for the actions he has committed if he is determined to be at fault. The aim to be achieved in this research is to find out and explain unlawful acts in cases of land grabbing without ownership rights and to find out the judge's analysis in the decision in case Number 76.PK.Pdt/2021 concerning land grabbing. In land disputes between parties who lose in court, the State must also be present to fulfill a sense of justice for the losing party, which means that land and building taxes or land documents that have been paid by the losing party are of course replaced or returned.